Study The Reality Of Neuromarketing In Syrian Commercial Organizations - Alabdeen, Dania Zen; Naim, Mones (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This research aims to study the reality of Neuromarketing applying in Syrian commercial organizations (the consumer's Attitudes towards Neuromarketing, and his Word of Mouth towards it) The research paper adapts the descriptive approach. A questionnaire has been developed to collect primary data from the research sample, which is a sample of 550 of Syrian commercial organizations' consumers. 515 valid questionnaires have been returned, which then have been analyzed by using some Statistical tools provided by the statistical program SPSS, like: Means, Skewness, and T-test. The most important research paper's results are represented in: the applying of Neuromarketing can generate a positive attitudes for Syrian consumers, the Syrian consumer tends to be a part of Neuromarketing researches, the Syrian consumer tends to take up the Word of Mouth concept towards organizations that will apply Neuromarketing. .The researcher also made a number of recommendations, including: Disseminating consumer knowledge towards Neuromarketing concept. هدَف البحث إلى دراسة أهم متطلبات تطبيق التسويق العصبي في المنظمات التجاريّة السورية (موقف المُستهلك السوري من تطبيق بحوث التسويق العصبي، تبني المُستهلك السوري لمفهوم الكلمة المنطوقة). اعتمد الباحث على المنهج الوصفي التحليلي, وقام بتطوير استبانة لجمع البيانات الأولية عن مفردات عيّنة البحث, والّتي هي عبارة عن عيّنة ميَسّرة من المُستهلكين السّوريين, قام الباحث بتوزيع 550 استبانة, استرد منها 515 صالحة للتحليل الإحصائي, وقد استخدم لتحليلها مجموعة من الأدوات الإحصائيّة الّتي يوفّرُها البرنامج الإحصائي SPSS, وأهمّها: المتوّسط الحسابي, معامل الالتواء, واختبار T- Test. فكانت أهم النتائج: إن تطبيق بحوث التسويق العصبي في المنظمات التجارية السورية يولّد موقفاً إيجابياً لدى لمستهلك السوري, تقبُل المستهلك لفكرة المشاركة في بحوث التسويق العصبي, حيث بلغ متوسط إجابات أفراد العينة(3.359), تبني المستهلك السوري لمفهوم الكلمة المنطوقة تجاه المنظمات التجارية التي ستُطبق بحوث التسويق العصبي, وتقدّم الباحث بمجموعة من التوصيات, منها: التركيز على نشر ثقافة التسويق العصبي لدى المستهلك السوري بشكل أوسع, بُغية تدعيم موقفه الإيجابي.